『현대 한국어 동사 구문사전』 거시구조 기술의 문제 - 김현권(Hyunkwon Kim) (언어학, 2016)
The aim of the present study is to complement the list of modern Korean verb lexicon by Song et al.(2014-16). Each verb entry has its counterpart in various types in the verb lexicon, and their syntactico-semantic correlations should be represented systematically in the microcstructure. For the systematic and coherent establishment of the verb entries in the macrostucture, we have examined the possibility of substituting of the support verb ‘ha’ in the compound verb type ‘noun+ha’ with all the other support verbs which would bring changes of meaning and of syntactic constructions. This aspect of the investigation is followed by the analysis of verb compounds or verb chains of the type V+V, which together will eventually contribute to a better Korean verb construction dictionary. KCI Citation Count: 1